Teaching the majority : breaking the gender barrier in science, mathematics, and engineering - Rosser, Sue Vilhauer (New York : Teachers College Press, 1995)
The physical sciences, mathematics, and engineering persists as the professional areas where women have not yet broken the gender barrier. Mainstream scientists are realizing that they must rethink the way science is taught if they are to attract more peopele, particularly more women, to the sciences. The interest in and demand for this information will make this book indispensable. .
Reaching the majority : retaining women in the pipeline -- Physics and engineering in the classroom -- A feminist approach to teaching quantum physics --Culturally inclusive chemistry -- The Clare Boothe Luce Program for Women in Science at Creighton University -- The four-component system : a nontechnological interactive learning environment where women count -- Toward a feminist algebra -- Girls and technology : villain wanted -- Accommodating diversity in computer science education -- Attracting and retaining women in graduate programs in computer science -- Female-friendly geoscience : eight techniques for reaching the majority -- Female-friendly environmental science : building connections and life skills -- No classroom is an island -- Conclusion. Changing curriculum and pedagogy to reach the majority results in a positive upward spiral.
Includes bibliographical references and index.
Keywords: ENGINEERING EDUCATION